2002
DOI: 10.1061/(asce)0733-9445(2002)128:9(1222)
|View full text |Cite
|
Sign up to set email alerts
|

Axial Load Behavior of Stiffened Concrete-Filled Steel Columns

Abstract: This study investigates the axial load behavior of concrete-filled steel tubular ͑CFT͒ columns with the width-to-thickness ratios between 40 and 150, and proposes an effective stiffening scheme to improve the mechanical properties of square cross-sectional CFT columns. Seventeen specimens were tested to examine the effects of cross-sectional shapes, width-to-thickness ratios, and stiffening arrangements on the ultimate strength, stiffness, and ductility of CFT columns. Moreover, nonlinear finite element analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(99 citation statements)
references
References 7 publications
(1 reference statement)
3
73
0
8
Order By: Relevance
“…최영환 [4] 은 현행 규준 [2], [3] 에서 제시하는 제한치 이상의 판폭두께비를 지닌 폭두 께비 60∼100의 CFT단주 기둥을 제작하여 중심축하중 실 험을 수행하였다. 중심축하중 실험을 통해 CFT기둥에서의 좌굴 후 내력의 상승을 확인하였고, 기존 규준 [2], [3] [5], [6], [7], [8] 기존의 연구내용 [5], [6], [7], [8] 과는 달리 박재우 [9] 선행연구 [5], [6], [7], [8] 와는 달이 본 연구에서는 폭두께비가 [12] 결과는 Table 3에 정리하였고(단, 괄호 안의 치수는 실제치수임), CFRP쉬트에 대한 재료시험 [13] 결과는 Table 4에 각 실험체의 최대내력은 Table 5에 정리하였다. 또한 …”
Section: Fig 2 the Concept Of Local Buckling Delayed By Cfrp Sheetsunclassified
“…최영환 [4] 은 현행 규준 [2], [3] 에서 제시하는 제한치 이상의 판폭두께비를 지닌 폭두 께비 60∼100의 CFT단주 기둥을 제작하여 중심축하중 실 험을 수행하였다. 중심축하중 실험을 통해 CFT기둥에서의 좌굴 후 내력의 상승을 확인하였고, 기존 규준 [2], [3] [5], [6], [7], [8] 기존의 연구내용 [5], [6], [7], [8] 과는 달리 박재우 [9] 선행연구 [5], [6], [7], [8] 와는 달이 본 연구에서는 폭두께비가 [12] 결과는 Table 3에 정리하였고(단, 괄호 안의 치수는 실제치수임), CFRP쉬트에 대한 재료시험 [13] 결과는 Table 4에 각 실험체의 최대내력은 Table 5에 정리하였다. 또한 …”
Section: Fig 2 the Concept Of Local Buckling Delayed By Cfrp Sheetsunclassified
“…However, concrete-filled square or rectangular steel tubes have their own advantages including convenient beam-to-column connection, high moment capacities, and aesthetic consideration [6]. As a way to improve the confinement of square or rectangular tubes, some researchers have utilized welded longitudinal stiffeners on the inner or outer wall of square or rectangular steel tubes [7][8] or transverse stiffeners (welded or bolted binding bars at the wall of tube) arranged at an spacing along the longitudinal axis of the steel tubes [9][10]. The main test results revealed that the longitudinal and transverse stiffeners are effective in delaying local buckling and enhancing bearing capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The CFRT column-to-beam connections are broadly classified into two categories [4]. The most convenient way is directly attaching the steel beam to the column tube or through the diaphragm plate.…”
Section: Introductionmentioning
confidence: 99%